Informal assessment tools in kindergarten - Hillyard, Sarah (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
In all contexts, assessment is intended to inform and improve learning and teaching. Because of the characteristics of very young learners and of the teaching and learning process in kindergarten, assessment should be carried out in normal everyday activities while learning is happening. Therefore, it is essential for assessment tools to allow for continuous and on-going assessment as children develop and demonstrate their achievements over time. This article explores the principles of assessment and examines an informal assessment tool for carrying out observations that is suitable for assessing very young learners in EFL contexts.